The Effectiveness of the Kolb Learning Method in Preventing Baby Blues Syndrome in Postpartum Mothers through a Neurobiological Approach - Lia Idealistiana; Ita Herawati; Sugiarti; Siti Nurjannah; Cunayah; Anisa Yulianti (Postgraduate, University of Mataram, 2024)
This study aims to evaluate the effectiveness of the Kolb Learning method in preventing baby blues syndrome in postpartum mothers through a neurobiological approach. Baby blues syndrome is often caused by a sudden drop in hormones after giving birth, which can affect the new mother's neurobiological balance and mental health. Providing public education through the Kolb Learning method, which emphasizes experience-based learning and understanding of biological changes after childbirth, is expected to be able to prevent this disorder. This quasi-experimental research involved 120 postpartum mothers, divided into two groups: control and treatment in each BPM. The research results showed that the Kolb Learning method was significantly effective in preventing baby blues syndrome, with 100% of respondents in the treatment group not experiencing the syndrome. The simple t-test showed significant results with a p value = 0.000, strengthening the effectiveness of this intervention. These findings indicate that a neurobiological approach using the Kolb Learning method can be an effective intervention to prevent baby blues syndrome during the postpartum period. Therefore, it is recommended that this method be integrated into antenatal education programs to improve the psychological and biological well-being of mothers after giving birth.